Visual Search for Circumscribed Interests in Autism Is Similar to That of Neurotypical Individuals - Silver, Benjamin M.; Conte, Mary M.; Victor, Jonathan D.; Jones, Rebecca M. (Frontiers in Psychology, 2020)
Intense interests are a core symptom of autism spectrum disorders (ASD) and can be all-encompassing for affected individuals. This observation raises the hypothesis that intense interests in ASD are related to pervasive changes in visual processing for objects within that category, including visual search. We assayed visual processing with two novel tasks, targeting category search and exemplar search. For each task, three kinds of stimuli were used: faces, houses, and images personalized to each participant’s interest. 25 children and adults with ASD were compared to 25 neurotypical (NT) children and adults. We found no differences in either visual search task between ASD and NT controls for interests. Thus, pervasive alterations in perception are not likely to account for ASD behavioral symptoms.